Chatter Prediction for Variable Pitch and Variable Helix Milling - Yong Wang; Taiyong Wang; Zhiqiang Yu; Yue Zhang; Yulong Wang; Hengli Liu (Shock and Vibration)
Regenerative chatter is a self-excited vibration that can occur during milling, which shortens the lifetime of the tool and results in unacceptable surface quality. In this paper, an improved semidiscretization method for modeling and simulation with variable pitch and variable helix milling is proposed. Because the delay between each flute varies along the axial depth of the tool in milling, the cutting tool is discrete into some axial layers to simplify calculation. A comparison of the predicted and observed performance of variable pitch and variable helix against uniform pitch and uniform helix milling is presented. It is shown that variable pitch and variable helix milling can obtain larger stable cutting area than uniform pitch and uniform helix milling. Thus, it is concluded that variable pitch and variable helix milling are an effective way for suppressing chatter.